FISH APARTMENT AS AN EFFORT TO INCREASE PRODUCTIVITY AND CONSERVATION OF FISH RESOURCES (LITERATURE REVIEW) - Yuli Andriani; Ayi Yustiati; Rajib Bussalam; Yuliana Farahita; Halyda Aulia; Rahma Balqis (Universitas Mataram, 2024)
The decline in global marine fisheries production has sparked concerns about depletion of fish resources. The innovation developed is the use of fish apartments to increase productivity and conserve fish resources. Fish apartment is useful as fishing media, replacement habitat for damaged coral reefs, nursery ground and feeding ground for fish habitat ecology. Fish apartment can also be an indicator of changes in trophic levels in the food chain in aquatic ecosystems. This research explores the benefits of fish apartment for increasing productivity and conserving fish resources. Descriptive and exploratory research methods were carried out by combining literature and published research results. The benefits of fish apartment as an effort to increase the productivity of fish resources can be seen from the existence of waters that have the potential to become fishing areas which contribute to increasing fish stocks so that catches increase by 80% per year from 2013-2015. The fish apartment can restore damaged aquatic ecosystems because it increases the abundance of 39 types of fish species and improves the fish habitat for the 20 families of coral fish that occupy the fish apartment.